Residual effects of lime and phosphorus sources in pastures on cerrado soil - Sanzonowicz, Cláudio; Lobato, Edson; Goedert, Wenceslau J. (Pesquisa Agropecuaria Brasileira, 2014)
The residual effect of five sources of phosphate combined with three levels of lime were evaluated during ten years in a field experiment in a Dark Red Latosol (Haplustox). There was response from Brachiaria decumbens to the highest level of P applied, and the greatest increment occurred between 38 and 150 kg/ha of P. The phosphate efficiency on the total production of dry matter was as follows: single superphosphate (SS) = thermalphosphate (Yoorin) > rock phosphate (RF) from Gafsa/Tunisia hyperphosphate = RF from North Carolina > RF from Araxá. The efficiency of the Araxá RF was low at the beginning, but increased with time and with higher rates. At the 38 kg/ha level of P applied in the form of RF from Araxá, yields were not greater than the control, and other sources at the same P level had their residual effects disappeared after the RF year. All P sources showed residual effects at the highest levels. There was lime effect. Liming affected the natural phosphate performance only in the first year. The surface application of SS showed better yields than those obtained with the incorporation of the same amount of P at transplanting. Values of P in soil were smaller using Mehlich extractant compared to Bray I for all sources and levels. However, for the natural phosphate from Araxá at the highest level, the Mehlich method overestimated available P.